THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND COMPANY CHARACTERISTICS ON EARNINGS PERSISTENCE - Aida Afriyanti; Putri Nurmala; Akhmad Sigit Adiwibowo (EAJ (Economic and Accounting Journal), 2022)
This study aims to determine the effect of Corporate Social Responsibility and Company Characteristics on Earning Persistence in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 – 2020. The sample used is 20 companies from 62 food and beverage companies listed on the Stock Exchange. The Indonesian Stock Exchange (IDX) for the 2016 – 2020 period. The research sample was taken by purposive sampling or by setting certain criteria. Methods This research uses secondary data types with a quantitative approach. The hypothesis test conducted in this study is the Classical Assumption Test, R2 Test, F Test, and t Test using the Eviews 9 program. Simultaneous test results show that corporate social responsibility variables and company characteristics have a significant effect on earnings persistence. The partial test results show that the corporate social responsibility variable has no effect on earnings persistence, while the company characteristics variable (ROA) has a significant effect on earnings persistence.